DESAIN MEDIA PEMBELAJARAN DALAM PENDIDIKAN AGAMA ISLAM (PAI) - Suseno, Suseno; Ritonga, Supardi (STKIP Pesisir Selatan, 2025)
The design of instructional media in Islamic Religious Education (PAI) is a fundamental element in supporting an effective and meaningful learning process. Media serves not only as a technical aid but also as a strategic means to transform Islamic values into contextual and relevant messages for students in line with the demands of contemporary times. In today’s digital era, learning media must be designed creatively, innovatively, and adaptively to foster students’ learning interest, deepen their understanding of Islamic teachings, and shape their Islamic character. This study aims to examine the key principles of instructional media design in the context of PAI learning and to analyze the challenges faced by teachers in developing and implementing such media. Using a descriptive qualitative approach based on a literature review, this article offers a comprehensive overview of how instructional media can be structured to address the integrative needs of cognitive, affective, and psychomotor domains. The findings indicate that effective PAI media design should consider alignment with learning objectives, the characteristics of learners, contextual Islamic values, and the wise utilization of digital technology.